1992
DOI: 10.1104/pp.100.1.416
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Induction of Osmotic Stress-Responses

Abstract: In Mesembryanthemum crystallinum, salt stress induces the accumulation of proline and a specific isoform of the enzyme phosphoenolpyruvate carboxylase (PEPCase) prior to the switch from C3 to Crassulacean acid metabolism (CAM). To determine whether plant growth regulators initiate or imitate these responses, we have compared the effects elicited by NaCI, abscisic acid (ABA), and cytokinins using PEPCase and proline levels as diagnostic tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
34
2
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(43 citation statements)
references
References 43 publications
6
34
2
1
Order By: Relevance
“…It was reported that the exogenous addition of ABA resulted in the accumulation of PEPCase and in the switch to CAM (the criteria being elevated PEPCase activity and malic acid levels) under particular growth conditions (3). This observation differed from results obtained under previously described growth conditions (16), where a rise in ABA was not required for PEPCase mRNA induction (16). To resolve this discrepancy, we have reinvestigated the combined effects of salt and ABA on the expression of PEPCase under varying light conditions in this halophyte.…”
contrasting
confidence: 54%
See 3 more Smart Citations
“…It was reported that the exogenous addition of ABA resulted in the accumulation of PEPCase and in the switch to CAM (the criteria being elevated PEPCase activity and malic acid levels) under particular growth conditions (3). This observation differed from results obtained under previously described growth conditions (16), where a rise in ABA was not required for PEPCase mRNA induction (16). To resolve this discrepancy, we have reinvestigated the combined effects of salt and ABA on the expression of PEPCase under varying light conditions in this halophyte.…”
contrasting
confidence: 54%
“…Plants were grown on a 16-h/d cycle at 280C under low intensity fluorescent lights (300 ,gE m-2 s-') until 6 weeks of age. At this time, the plants were divided into three groups and each group was exposed to a different light treatment at 280C on a 16 ,gE m-2 s-1 measured. Each light regime included control plants grown in Hoagland solution, plants exposed to 10 ,gM ABA for the 7-d period of the light treatment, and plants exposed to 400 mm NaCl for 30 h (starting on the sixth d of the light treatment).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endogenous increases or exogenous application of ABA result in CAM induction (Dai et al, 1994;Taybi et al, 1995) by stimulating increased expression of key CAM enzymes such as PEPC (Chu et al, 1990;Dai et al, 1994;Taybi et al, 1995), enolase (Forsthoefel et al, 1995a), phosphoglyceromutase (Forsthoefel et al, 1995b), and vacuolar ATPase subunit c (Tsiantis et al, 1996). Other plant growth regulators such as cytokinins have been shown to either suppress or enhance PEPC expression depending on the mode of application (Schmitt and Piepenbrock, 1992;Thomas et al, 1992;Thomas and Bohnert, 1993;Dai et al, 1994;Peters et al, 1997). Cytokinin applied to roots causes an enhancement in PEPC expression, whereas foliar application of intact plants or feeding to detached leaves suppresses PEPC expression and prevents PEPC induction by drought or salinity stress (Schmitt and Piepenbrock, 1992;Dai et al, 1994;Peters et al, 1997).…”
mentioning
confidence: 99%